Differences between macrovascular and microvascular functions in pregnant women with chronic hypertension or preeclampsia: new insights into maternal vascular health - Kaihara, Julyane N. S. [UNESP]; Grepi Okano, Hellen Cristiane; Veiga, Eduardo Carvalho de Arruda; Tallarico, Gustavo Moleiro; Dias-Junior, Carlos Alan [UNESP]; Cavalli, Ricardo Carvalho; Sandrim, Valeria Cristina [UNESP] (Frontiers, 2025)
Introduction: Hypertensive disorders of pregnancy, including chronic hypertension (CH) and preeclampsia (PE), stand as prominent global contributors to maternal and perinatal morbidity and mortality. Endothelial dysfunction plays a central role in the pathophysiology of these conditions. This dysfunction impacts blood flow and the regulation of vascular response, potentially leading to alterations in the remodeling of blood vessels. Nitric oxide bioavailability, a key regulator of vascular tone, is often diminished in endothelial dysfunction, with nitrite levels serving as a surrogate marker. Methods such as pulse wave velocity (PWV) and peripheral arterial tonometry provide valuable insights into vascular health in large and small vessels, respectively, in hypertensive pregnancies. Among these, peripheral arterial tonometry stands out as a less explored technique in research. This study aimed to evaluate potential alterations in the macrovascular arterial stiffness and the microvascular endothelial function among pregnant women diagnosed with CH or PE compared to healthy pregnant (HP) women. Additionally, we aimed to correlate these vascular parameters with demographic and clinical data. Methods: The study enrolled 24 HP women, 24 with CH during pregnancy, and 24 with PE who underwent evaluations of large-artery stiffness via PWV assessments and peripheral arterial tonometry via natural logarithm of the reactive hyperemia index (lnRHI) assessments. Results: Patients with CH and PE exhibited higher large-artery stiffness than HP, although the lnRHI values remained comparable across all groups. Furthermore, PWV values demonstrated a direct correlation or tendency toward a positive correlation with systolic and diastolic blood pressures (SBP and DBP) in all groups. However, PWV and nitrite concentrations were not correlated. Notably, microvascular function was positively correlated with SBP and DBP in PE, but not in CH or HP. The correlation between lnRHI and nitrite concentrations was observed in the PE group. Conclusion: Thus, our findings indicate that, while HDPs have demonstrated increased large-artery stiffness in comparison to HP, the microvasculature analyzed by peripheral arterial tonometry was similar among all three groups. Interestingly, the correlation patterns in the nitrite levels, blood pressure, and microvascular function differed in the PE and CH groups.
Keywords: arterial stiffness; chronic hypertension in pregnancy; endothelial dysfunction; peripheral arterial tonometry; preeclampsia; pulse wave velocity